Natives helping foreigners? The effect of inoculation of poplar with patagonian beneficial microorganisms - Mestre, María Cecilia; Pastorino, Mario Juan; Aparicio, Alejandro Gabriel; Fontenla, Sonia Beatriz (2018)
Inoculation with microorganisms represents an opportunity to enhance tree production, directly affecting plant growth or survival at planting. The aim of the present study was to evaluate the effect of mixed inoculation with native mycorrhizae, two yeasts and one endophytic bacterium, on the growth of two poplar clones commonly used in Patagonia, Argentina. Yeasts and bacteria were selected base on their ability to produce IAA and siderophores, as well as P solubilization in-vitro. A greenhouse trial was performed using hardwood cuttings of Populus nigra ‘Italica’ and Populus trichocarpa ‘SP1456’. Only yeasts modified growth traits, in a host-related response: Tausonia pullulans reduced the root/shoot ratio in P. nigra, and Candida saitoana and increased shoot dry biomass in P. trichocarpa. All plants presented arbuscular mycorrhizal colonization but ectomycorrhizae were absent. Two types of arbuscular mycorrhizal colonization were observed, one of them similar to Glomus tenue. We found a tendency for a higher percentage of arbuscular mycorrhizal colonization when plants were inoculated with T. pullulans. The used of native yeast along with mycorrhizal inocula appears to be a promising tool to improve poplar forestry.